Auto/não-auto discriminação de raízes e o reconhecimento parental de Eucalyptus urophylla sob diferentes condições ambientais - Bertoli, Suzana Chiari [UNESP] (2015)
Plant abilities such as kin recognition and self/non-self discrimination have gained more attention lately. This latter indicate that plants can discriminate the roots of other plants (non-self) of its own (self), increasing competition with non-self and avoiding the root proliferation with self. However, we don't have much knowledge about how the environmental conditions affect these phenomena. In this study, we estimate if the degree of relatedness in a single species can affect the self/non-self discrimination roots, and if the kind of behavior (competition and facilitation) between plants with high and low degree of relatedness may be influenced by environmental condition. Split-root of clonal plants (high degree of relatedness); half-brothers plants (intermediate degree of relatedness); and population plants (low degree of relatedness) of Eucalyptus urophylla were planted so that each pot contained either two roots of the same plant (Sd) or of two different plants (NSd), arranged in triplets. As the degree of relatedness between individuals was increased, the discrimination ability was decreased, indicating that the genetic relatedness affected the root discrimination. Contrary to expectations, NSd didn't increase the root proliferation compared to Sd for the most treatments tested, but significantly affected many other growth traits. In clonal and population groups, the manner and strength that these changes occurred in response to the root interaction was regulated by different environmental conditions. A lower competitive behavior was observed when clonal plants interact by the roots in non-restrictive environments, but under water deficits the competition was increased. In low degree of relatedness plants, the competition was increased by non-restrictive environment, but reduced under limited resources availability (water and nutrients). Our results showed that self/non-self root discrimination and the competitive behavior ...